Penerapan Model Pembelajaran Mastery Learning Untuk Meningkatkan Prestasi Belajar Matematika Siswa Kelas IXB SMP Negeri 3 Selat - I Nyoman Mulyadi (Jayapangus Press, 2019)
Problem Formulation of this research is the Application of Mastery Learning Learning Model to Increase Mathematics Student Achievement in Class IXB First Semester 3 Strait Middle School in 2018/2019 Academic Year The purpose of this study is to improve mathematics learning achievement of class IX B students of SMP Negeri 3Selat in semester I, year 2018/2019 lessons. The place for this classroom action research is in the 3 Strait Middle School, by taking the research subject of class IX B students in the first semester of the 2018/2019 academic year. The object of this class action research is an increase in Mathematics learning achievement of students of class IX B of 3 Strait Middle Schools, 2018/2019 Academic Year. The average value of 51.61 in the first cycle and in the second cycle rose to 77.58. The application of Mastery Learning Learning Model to Improve Mathematics Learning Achievement is effectively applied in the learning process which results in students being active, enthusiastic, critical thinking and able to understand the material being taught so that students' learning achievement increases.